INTERNATIONAL EFFORTS TO COMBAT CYBERCRIME - Dr. Baqer Musa Saeed AL_khafagy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Today, we are living in the period of data and correspondence innovation, which has become the premise on which all fields rely upon, and for all establishments, regardless of whether they are public foundations claimed by state governments or private organizations possessed by people, the data innovation in the administration of administrations and correspondence networks is the essential device on the way. This has been the quick advancement of data and correspondence innovation and the Internet has driven the entire world to the rise of new examples of wrongdoings got through the misuse of the innovation, which came about with the formation of another criminal marvel, a wrongdoing identified with robotized computer and the Internet, which is made by assaults and forward leaps and penetration inside Information frameworks with the end goal of either pulverizing those frameworks or acquiring private data, regardless of whether military or financial, which cautions that there are hazards at the worldwide and public levels if this wonder isn’t tended to, which will bring about military and social misfortunes, on the off chance that they are left to the general public. This requires - and this is the situation - discovering approaches to address this wonder. Digital ??crimes are violations over the Internet that depend on invasion into unapproved sites to enter, with the point of disturbing or crushing the information accessible on them or holding onto them, and it is a progression of digital assaults did by another state.